Configuration Of Molecular Imprinted Polymers For Specific Uptake Of Pharmaceutical In Aqueous Media Through Radical Polymerization Method - Mohd Amri, Mohammad Hanif (Universiti Sains Malaysia, 2021)
Precipitation polymerization method was used to prepare molecularly imprinted polymers (MIP) for the uptake of acetaminophen in aqueous media. Acetaminophen, methacrylic acid (MAA), ethylene glycol dimethacrylate (EDGMA), 1,1’- Azobis (cyclohexanecarbonitrile) (ABCN) were used as template, functional monomer, cross-linker and intiator respectively. The molarity of cross-linker and functional monomer were varied for the study of imprinting effect of MIPs. High concentration of cross-linker exhibit poor binding ability of MIPs while high molarity of monomer demonstrate better performance in binding capacity. The optimum MIP was observed from template:monomer:cross-linker molar ratio at 1:58:15 with binding capacity of 3.68 mg/g polymer. Next, pristine PES and molecularly imprinted membrane (MIM) were fabricated using phase inversion method. MIM was prepared by adding optimum MIPs in casting solution for the study of antifouling properties as compared to pure membrane. The relative flux of MIM has showed a poor antifouling behaviour in real wastewater sample while a good performance in synthetic solution. However, MIM and pristine membrane have revealed better rejection of acetaminophen in wastewater at 71.31 and 73.06% respectively.